(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2020)
During the past centuries high level of agricultural production resulted in a significant decrease steppe vegetation. In transformed landscapes South Ukraine cultural monuments such as old settlements can have the potential for biodiversity conservation. During the last decade (2010–2019) the flora of 18 earthworks of the Lower Dnipro ancient settlements with varied area from 1.1 to 18.7 ha was investigated. All settlements located on the steep bank of the Dnipro River on both sides (Kherson and Mykolayiv Regions), mainly between two closely spaced ravines or «balkas». The river terrace and ravines provided a natural protection for the settlements on three sides, and on the another side they were protected by artificial moat and shaft. The Dnipro was acknowledged as playing a key role in specific location of the earthworks as a leading waterway for trade and economic structure formation in the classical and Hellenistic periods. A list of the flora of vascular plants includes 526 species wich belongs to 279 genera, 74 families, 3 classes and 2 divisions. Total species richness ranged from 125 to 290 (178 species per archeological site in average). An appreciable number of native plants indicate a hight level of preservation of the objects. The contribution of native species in old settlements varied much from 62.1% (Liubymivske) to 81.1% (Velyke Tiagynske). The contribution of native species to the alien species is 3:1. Beside this, in the study area, we identified 30 species of protected vascular plants, of which 10 plant species are included in the Red Data Book of Ukraine (Astragalus borysthenicus, A. dasyanthus, Elytrigia stipifolia, Gymnospermium odessanum, Stipa capillata, S. lessingiana, S. pulcherrima, S. ucrainica, Tulipa biebersteiniana, T. gesneriana) and 20 plant species are included in the Red List of Kherson Province: Amygdalus nana, Bellevalia sarmatica, Bromopsis heterophylla, Dianthus andrzejowskianus, Ephedra distachya, Ferula capsica, Fraxinus excelsior, Hyacinthella leucophaea, Jurinea salicifolia, J. stochadifolia, Limonium platyphyllum, Linaria macroura, Linum czernjajevii, Prangos odontalgica, Quercus robur, Silene supina, Valeriana stolonifera, Veronica capsellicarpa, Vinca herbacea, Vitis sylvestris.